Mental health status and its influencing factors in middle school students under the regular prevention and control of COVID-19 - Zhao Songtao; Li Liping; Sun Zhenxiao; Liu Zhendong; Zhao Lin; Chen Fangxia (Sichuan jingshen weisheng, 2023)
ObjectiveTo analyze the mental health status and its influencing factors in middle school students under the regular prevention and control of COVID-19， so as to provide references for the intervention and management of their mental health problems.MethodsFrom March 7 to 21， 2021， a stratified random sampling method was used to select 19 352 students from 17 schools in 3 districts and 9 counties of Linyi City， Shandong Province. Basic data were collected through a self-designed questionnaire. All students completed the Symptom Checklist 90 （SCL-90） to assess their mental health status. Then the factors affecting the mental health status of middle school students were screened using independent sample t-test， one-way ANOVA test and multiple stepwise regression analysis.Results① A total of 6 350 （32.81%） middle school students were found to have mental health problems. ② Each SCL-90 factor score and total average score yielded statistical difference among middle school students of different genders， relationships with classmate， closeness to friends， concerns about the epidemic， and pressure exerted by schoolwork （P<0.01）. Each SCL-90 factor score and total average score of middle school students were significant different in terms of the hours of smartphone usage for recreation per day， sleep duration per night in hours and exercise frequency （P<0.01）. ③ Multiple stepwise regression analysis denoted that female gender， poor relationship with classmate， no close friend and long hours of smartphone usage for recreation were the risk factors for mental health of middle school students （β=0.096， 0.183， 0.064， 0.232， P<0.01）.ConclusionThe prevalence rate of mild mental health problems is quite high among middle school students under the regular epidemic prevention and control. Additionally， female gender， poor relationship with classmate， no close friend and long hours of smartphone usage for recreation have a negative impact on middle school students' mental health.